Tradução, adaptação cultural e análise da confiabilidade da versão brasileira do questionário de reabilitação para o trabalho: WORQ - Fernandes, Susi Mary de Souza (2017)
The impact of disabilities is an important question in the work disabilities area. The functional capacities of a person with disabilities must be understood and inclusion mechanisms must be created in the attempt of perfecting performances and insuring egalitarian functions. The Work Rehabilitation Questionnaire (WORQ) is an instrument based on the International Classification of Functioning, Disability and Health (ICF) which proposes to evaluate the functionality in people with disabilities working or in vocational rehabilitation, however, it is not validated in Brazil. This study goal is to translate, and do the cross-cultural adaptation of the versions by interviews and self-report of The Work Rehabilitation Questionnaire (WORQ) and analyze the reliability of the version applied by interviews with the disabled workers inserted in the workplace by the Brazilian Inclusion Law. The translation and cross-cultural adaptation follow the international recommendations: translation, synthesis of the translations, and back-translation of the synthesis, analysis by the experts committee, pre-test, back-translation and pilot test. The analysis stage engaged 05 judges and the pre-test 14 possible users. The agreement rate was smaller than 90% only in the idiomatic equivalence that resulted in small modifications which did not changed the construct of the instrument. To test the reliability it was verified the stability (test-retest), equivalence (inter-observers) and the internal consistency with 34 disabled person, mean age of 40,3 (SD±4,2) years old, both sexes, employees of an educational institution in São Paulo that fit in by the Brazilian Inclusion Law (8.213/91), by a mean period 10,3 (SD ±7,8) years. The participants were evaluated in two moments. The first one evaluated the internal consistency, the values from α of Cronbach were bigger than 80% in every domain and bigger than 90% for the total score. Fifteen days after the first research 20 disabled person chosen by randomly were reevaluated to analyze the stability and equivalence. The coefficient of correlation intra class (ICC) to stability was 82, 5% (p=0,008) e for equivalency was 95,4% (p<0,001). This study provides an instrument with great reliability, capable of answering to the domains of ICF and facilitating the inclusion and remanence of the person with disability in the job market.